2007
DOI: 10.1096/fj.06-6169com
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose intracerebroventricular administration of galactocerebrosidase improves survival in a mouse model of globoid cell leukodystrophy

Abstract: Globoid cell leukodystrophy (GLD), also known as Krabbe disease, is a devastating, degenerative neurological disorder. It is inherited as an autosomal recessive trait caused by loss-of-function mutations in the galactocerebrosidase (GALC) gene. Previously, we have shown that peripheral injection of recombinant GALC, administered every other day, results in a substantial improvement in early clinical phenotype in the twitcher mouse model of GLD. While we did detect active enzyme in the brain following periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 26 publications
6
48
0
Order By: Relevance
“…The extension of lifespan reported here is moderate and in line with that observed in Twi mice that underwent other CNS-directed treatments, i.e. transplantation of gene-corrected neural stem cells (NSCs) (15) or mesenchymal stem cells (16), intratechal administration of recombinant GALC (49), and likely reflects failure of these approaches to provide sufficient levels of functional enzyme to correct the somatic pathology and particularly the PNS, which is likely the ultimate cause of lethality in this mouse model. In fact, treatments able to correct the systemic disease associated with GLD, such as HCT, alone or in combination with systemic delivery of GALC-expressing vectors (14,2023) as well as novel HSC GT protocols (50), significantly extend the lifespan of relevant GLD models.…”
Section: Discussionsupporting
confidence: 86%
“…The extension of lifespan reported here is moderate and in line with that observed in Twi mice that underwent other CNS-directed treatments, i.e. transplantation of gene-corrected neural stem cells (NSCs) (15) or mesenchymal stem cells (16), intratechal administration of recombinant GALC (49), and likely reflects failure of these approaches to provide sufficient levels of functional enzyme to correct the somatic pathology and particularly the PNS, which is likely the ultimate cause of lethality in this mouse model. In fact, treatments able to correct the systemic disease associated with GLD, such as HCT, alone or in combination with systemic delivery of GALC-expressing vectors (14,2023) as well as novel HSC GT protocols (50), significantly extend the lifespan of relevant GLD models.…”
Section: Discussionsupporting
confidence: 86%
“…Ommaya reservoir) would be necessary. Injection of replacement enzyme into ventricular CSF has been carried out in single-injection studies in mouse models of two other lysosomal storage disorders: Krabbe disease [14] and neuronopathic (type II/III) Gaucher disease [39]. Repeat-injection studies have been performed in mice with Niemann-Pick A, Sandhoff disease, neuronopathic Gaucher disease and MPS II [17,[39][40][41], and sustained enzyme delivery (using mini-osmotic pumps) has been explored in late infantile neuronal ceroid lipofuscinosis and metachromatic leukodystrophy mice [15,19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mouse and dog models of MPS IIIA [4][5][6][7][8][9][10][11], in addition to similar studies in other neurodegenerative lysosomal storage disorders, including MPS I [12,13], Krabbe disease [14], Batten's disease [15,16], Niemann-Pick A [17], fucosidosis [18], metachromatic leukodystrophy [19] and MPS II [20]; reviewed in [21], have indicated that intra-CSF injection of recombinant replacement enzyme is effective in reducing or preventing accumulation of primary and secondary substrates and, where assessed, ameliorating clinical disease. The injection site used in many of these investigations has been the cisterna magna, however, ventricular or intrathecal lumbar delivery is also possible, with the former under investigation in an enzyme replacement trial in children with a form of Batten's disease (NCT#01907087), and the latter being utilized in clinical trials in MPS I, MPS II, MPS IIIA and metachromatic leukodystrophy patients (NCT; #00852358; #01506141; #01299727; #0150028; #02060526).…”
Section: Introductionmentioning
confidence: 98%
“…Single dose intracerebroventricular (ICV) administration of GALC increased the Twi lifespan to an average of ~50 days. 31 This mild clinical effect may be due to enzyme turnover, as GALC enzyme is undetectable at the moribund stage. 32 Repeated enzyme injections are necessary to maintain a long-term functional pool of GALC enzyme.…”
Section: Single Modality Therapies For Murine Gldmentioning
confidence: 99%